A Benefit Dependency Network for Shadow Information Technology Adoption, Based on Practitioners’ Viewpoints - Scalabrin Bianchi, Isaías (2022)
Shadow information technology (SIT) revolves around systems that are hidden but are still managed by the same business entities. It consists of the use of devices, software, systems and applications without the information technology (IT) department’s approval. Employees use IT without the knowledge of the IT department, and it creates a gap in communications, as the IT department loses the knowledge of the reality within the company. However, there are benefits involved. In order to take advantage of these benefits, changes have to be implemented in the way that business activities are handled. The benefits should be a direct result of the changes, of the difference between the ongoing and the suggested way that activities should be undertaken, and the levels of efficiency and effectiveness to which people deliver their daily tasks. The objective of this study was to propose a benefit dependency network (BDN) for SIT, and, through its concepts, to synthetize our findings and specify the connections between SIT practices and their benefits. This research was conducted a systematic literature review (SLR) and used a design science research methodology, adopting semi-structured interviews with fourteen interactions to propose a BDN for SIT. We proposed a model with five dimensions related to a BDN for SIT. By understanding the BDN and the benefits of SIT, it is easier to have a better notion of the implications and the factors involved in order to assist the decision-making process. Whether an organization wants to reach innovation, increase revenue or retain clients, the BDN helps with analysis and selection, and is something that organizations should take seriously, as it is essential to have knowledge about what the benefits are and how they can be reached. To the best of the authors’ knowledge, this research included and replaced several processes in the BDN for SIT, in a topic that is still underexplored.